The Economic Impact of the Metro Manila (NCR) Enhanced Community Quarantine - Yu, Krista Danielle (Animo Repository, 2020)
Metro Manila (NCR) comprises 37.5 percent of the Philippine gross domestic product (GDP) and the 30-day enhanced community quarantine (ECQ) will cause a significant decline in the national economy. This policy brief is based on a persistent inoperability input-output model to estimate two metrics: inoperability and economic losses. This takes into account the interdependent nature of the different sectors of the economy and considers the impact of the pandemic on the productivity of sectors directly affected by the ECQ such as the manufacturing, construction, trade, finance, private sector services, and transport sectors. Unlike previous model, PIIM results will provide insights on the impact of the prolonged inoperabilities on the economy. Results show the degree by which each sector is affected and how much economic losses they incur. Such information will be essential in developing strategies for recovery.